2007
DOI: 10.1167/iovs.07-0014
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IGF-I Signaling in Retinal Endothelial Cells by Hyperglycemia

Abstract: This study demonstrates that hyperglycemic conditions enhance the response of RECs to IGF-I by increasing the association of IAP with SHPS-1 permitting the formation of the SHPS-1-Shc signaling complex, which is required for the proliferative response to IGF-I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 41 publications
4
46
0
Order By: Relevance
“…14 Little is known of the mechanism of action of β3 and angiogenesis. However, a recent study by Miller et al 23 showed that retinal endothelial cells in hyperglycemic conditions upregulate β3 ligand binding leading to an increase in its activation state, as measured by tyrosine phosphorylation, contributing to an enhanced responsiveness of retinal endothelial cells to insulin growth factor-I. In future, antagonists to the β3 integrin subunit may be used in models to assess its efficacy in inhibiting the angiogenic response.…”
Section: Discussionmentioning
confidence: 99%
“…14 Little is known of the mechanism of action of β3 and angiogenesis. However, a recent study by Miller et al 23 showed that retinal endothelial cells in hyperglycemic conditions upregulate β3 ligand binding leading to an increase in its activation state, as measured by tyrosine phosphorylation, contributing to an enhanced responsiveness of retinal endothelial cells to insulin growth factor-I. In future, antagonists to the β3 integrin subunit may be used in models to assess its efficacy in inhibiting the angiogenic response.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells express ␣v␤3, Src, p66 shc , and SHPS-1, which are required for studying SHPS-1 signaling complex formation and modulation of IGF-I signal transduction in hyperglycemia. In addition, they have been shown to respond to hyperglycemia by increasing their sensitivity to IGF-I stimulation (28,29). Therefore, we believe that this mechanism at least is applicable to specific cell types that have the capability to respond to hyperglycemic and/or oxidative stress with an increase in proliferation in response to IGF-I.…”
Section: P66mentioning
confidence: 95%
“…We chose endothelial cells because they express ␣V␤3, Src, p66 shc , and SHPS-1, the major components affecting SHPS-1 complex formation and IGF-I signal transduction, and they have been shown to respond to hyperglycemia by increasing their sensitivity to IGF-I stimulation (28,29). Similar to pSMC, IGF-I stimulated p66…”
Section: Sion Of P66mentioning
confidence: 99%
“…This leads to an increase in ligand occupancy of ␣V␤3, which in turn stimulates phosphorylation of the ␤3 -subunit (14). Blocking ␤3-subunit phosphorylation has been shown to inhibit hyperglycemia-induced changes in capillary permeability in vitro (15). Additionally, inhibition of ␣V␤3 in vascular endothelial and smooth muscle cells leads to decreased stimulation of both the MAPK and phosphoinoside-3 kinase pathways in response to IGF-I stimulation (14,15).…”
mentioning
confidence: 99%